2013
DOI: 10.1073/pnas.1214441110
|View full text |Cite
|
Sign up to set email alerts
|

LDL receptor and its family members serve as the cellular receptors for vesicular stomatitis virus

Abstract: Vesicular stomatitis virus (VSV) exhibits a remarkably robust and pantropic infectivity, mediated by its coat protein, VSV-G. Using this property, recombinant forms of VSV and VSV-G-pseudotyped viral vectors are being developed for gene therapy, vaccination, and viral oncolysis and are extensively used for gene transduction in vivo and in vitro. The broad tropism of VSV suggests that it enters cells through a highly ubiquitous receptor, whose identity has so far remained elusive. Here we show that the LDL rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
410
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 504 publications
(433 citation statements)
references
References 52 publications
19
410
1
3
Order By: Relevance
“…8 Indeed, in resting lymphocytes, LV postentry steps such as completion of reverse transcription, nuclear import, and chromosomal integration of the transgene do not readily occur. [8][9][10] Moreover, we confirmed low expression levels of the VSV receptor (ie, low-density lipoprotein receptor 11 ) at the surface of unstimulated CD34…”
Section: Introductionsupporting
confidence: 51%
“…8 Indeed, in resting lymphocytes, LV postentry steps such as completion of reverse transcription, nuclear import, and chromosomal integration of the transgene do not readily occur. [8][9][10] Moreover, we confirmed low expression levels of the VSV receptor (ie, low-density lipoprotein receptor 11 ) at the surface of unstimulated CD34…”
Section: Introductionsupporting
confidence: 51%
“…The enhanced effect in VSV-G mediated transduction could possibly be due to similar mechanism of viral entry mediated by GP64 and VSV-G as suggested previously [12]. It is also likely that widespread expression of LDL receptor and its family members that serve as major cell entry port for VSV [7], may provide a positive effect in VSV-G pseudotyped viral vectors. The observed variation in VSV-G mediated transduction efficiency in different cell types could be due to difference in receptor(s) expression.…”
Section: Discussionsupporting
confidence: 57%
“…To further investigate this question, we performed an additional antibody-blocking study. It was recently shown that the primary VSV receptor on mammalian cells belongs to the LDL receptor family and that VSV entry can be inhibited by preincubating target cells with an anti-LDLR antibody (45). We therefore tested the infectivities of VSV, Maraba virus, and VSV/Maraba G on K562-av␤3 cells that had been pretreated with this VSV receptor-blocking antibody or control measles virus receptor binding antibody (anti-CD46 antibody).…”
Section: Resultsmentioning
confidence: 99%